Epidemiology, types and clinical features of cases of ocular injuries attending a tertiary care teaching hospital of Eastern India - Naskar, Asok Kumar; Adhikari, Suman; Bandopadhyay, Sabyasachi; Mondal, Kanchan Kumar; Chakravorty, Asim; Sen, Sukanta (International Surgery Journal, 2018)
Background: Ocular trauma is one of the main causes of severe ocular morbidity. The goals of this study were to describe epidemiology, causations, clinical features of ocular trauma, to analyse visual outcomes of ocular trauma. Methods: The patient was enquired about the time of occurrence of the injury, place, types of injury inflicted, any prior trauma or surgery, any treatment received before attending to the hospital. Visual acuity of each eye was recorded by using Snellen’s chart. In patients with poor vision gross assessment was done by counting fingers at specific distance, hand movements, perception of light present or not, projection of rays- accurate or not. Ocular motility testing was done in all patients. Results: Patients suffering from ocular injuries in one or both eyes, were examined clinically at the eye department of R G Kar Medical College and Hospitals, Kolkata, from December 2011 through August 2012. Approximate 757 persons had injury in one eye and 100 had injuries in both eyes (totalling 957 eyes with injuries in 857 patients). Males, 640 (74.7%) had more number of injuries than females 217 (25.3%) and injury was more common between 21 and 50 years of age groups in both sexes. Conclusions: A significant burden of ocular trauma in the community requires that its prevention and early management be a public health priority.